Eating Behaviors and the Food Environment of Students with Overweight/Obesity from Different Higher Education Settings (OR08-06-19). (13th June 2019) - Ryan, Rachel; Kleiman, Jennifer; Mahmood, Miriam; Wong, Kayla; Lu, Ronald; Chen, Yufei; Bodas, Devika; Haisley, Quinn; Abdelmassih, Kelly; Fernandes, Nicolle; Bihuniak, Jessica
Abstract: Objectives: Emerging adults attending 2- and 4-year tertiary institutions are at high risk for weight gain/excess weight. Developing effective, tailored interventions requires an understanding of behavioral/environmental differences between student populations. The objective of this study was to describe eating behaviors/the food environment of students with overweight/obesity enrolled in 2- and 4-year tertiary institutions. Methods: Students ages 18–24, with a BMI ≥25, enrolled in LaGuardia Community College ( N = 41) or New York University ( N = 51) were recruited. Height and weight were objectively measured. Participants completed a Qualtrics survey, which included: 1) Produce Consumption Self-Efficacy (SEPC) subscale, 2) Fruit and Vegetable Consumption subscale, and 3) questions regarding usual meal location/meal preparer. Descriptive, Mann-Whitney U and chi-square analyses were conducted. Results: Ninety-two students (64.8% female, age = 19.6 ± 1.7, BMI 31.4 ± 5.8) from 2- and 4-year tertiary institutions completed the survey. Two year students were significantly older ( P = .0001), had a higher BMI ( P = .01), and scored higher on: self-reported consumption of at least 5 servings of fruit per day ( P = .01), self-efficacy for eating fruits and vegetables as a snack, even if everybody else were eating other snacks ( P = .02), and eating 9 half cups of fruits and vegetables each day ( P = .0002). A greater percentage of 4-year students reported eating most of their meals "in an on-campus dining hall" (53 vs. 28%; P = .04); while more 2-year students reported "my place of residence" (41 vs. 35%) or "on-the-go, which I previously prepared at home" (21 vs. 4%). Usual meal preparer differed between student populations ( P < .001); 4-year students were more likely to identify "the college/university I attend" (69 vs. 13%) while a greater percentage of 2-year students indicated "my parental figures" (38 vs. 4%) or "myself" (33 vs. 19%). Conclusions: Community college students tended to have a higher BMI, despite reporting higher fruit/vegetable consumption self-efficacy and being more likely to eat meals, prepared by themselves or their parental figures, at home or on-the go. Differences in eating behaviors, beliefs and meal conditions should be taken into account when designing weight loss interventions for these understudied, high-risk populations. Funding Sources: NYU College of Arts and Science Dean's Undergraduate Research Fund Grant (Spring 2018).